The emerging threat of Fall Armyworm in India time for proactiveand collective action - Padhee, A K; Prasanna, B M (Indian Farming, 2019)
The Fall Armyworm (Spodoptera frugiperda; commonly referred to as â€œFAWâ€)is a crop pest native to the Americas. It was first formally reported in West Africa in January 2016 and has spread to several countries across Africa (except a few countries in North Africa). The pest has been reported for the first time in India in Karnataka in July 2018, and subsequently in a few other states, such as Andhra Pradesh, Telangana, Tamil Nadu, Maharashtra and Odisha. The Indian Council of Agricultural Research (ICAR) â€“ National Bureau of Agricultural Insect Resources (NBAIR) issued a â€˜pest alertâ€™ on 30th July 2018 based on results of surveys conducted between 9-18 July 2018 that recorded more than 70% prevalence of the FAW in a maize field in Chikkaballapur, Karnataka. The pest later spread to eight to nine districts of Karnataka, such as Shivamogga, Bellary, Belgaum and Hassan. The FAW damage has been the highest in maize, while several other crops, such as sorghum, sugarcane, millets and vegetables are also vulnerable to the attack. The pest has caused significant concerns among the stakeholders and heightened the attention of the Government machinery.